Theatre for Social Transformation in Japanese, Chinese and Korean - Kaur, Kanwaljit (International Journal of Psychosocial Rehabilitation, 2024)
In the pre-modern world, theatre was a vibrant and massive presence. In the seventeenth century, Chinese scientist Li Liweng states, "The historical context of a ritual is determined by the performances it conveyed. As a result, while unique in some ways, playwriting is clearly not a minor skill. It ranks towards the top of the list, with history, diary, section, and stating "(78-79). In today's society, such a predicament for the presentation community has been tested and problematized. Today's execution scholars, like Philip Auslander, criticise the "standard, unreflective guesses" made about live executions. "Attempts to explain the value of liveness' [by] conjuring sayings and disarrays like 'the witchcraft of live theatre,' the 'energy' that presumably exists among performers and events in a live event, and the 'neighbourhood' live show is occasionally said to make among performers, moreover, eyewitnesses," says Auslander. Innovation has turned the world, and people themselves, into a'standing store' where anything and everyone is instrumental, a method for being spent or obliterated, rather than a completely present end in themselves, thanks to imaginative advancements in PC-based recreation and correspondences (Heidegger 3-35). Overall, postmodern speculation will consider theatre as a "fascinating and mistaken development in relation to a connected world" and will question if the live scene still exists (Fortier 220). This study is also concerned with theater's Leftist philosophy and its opposition to fundamentalist dramatic development. Farming, proficiency crusade, social concordance, young lady dealing, youngster labour, orientation separation, strict resistance, ladies strengthening, HIV-AIDS prevention, family planning, beat polio, sustenance, climate contamination, and so on are all issues that theatre in India emphasizes.